x(x² - 2x - 24)
x(x - 6)(x + 4)
2007-01-20 13:07:47
·
answer #1
·
answered by Jim Burnell 6
·
1⤊
0⤋
I'm assuming you want us to factor it.
Step 1) Always factor out x's
x^3 - 2x^2 - 24x = x(x^2 - 2x - 24)
Step 2) Find two numbers that add up to b (in this case, -2) and multiply to give c (in this case, -24). If the coefficient of x^2 wasn't 1, this step would be slightly different.
4+(-6)=-2, 4*-6=-24
Step 3) Write down the factored form (x plus first number times x plus second number)
(x+4)(x-6)
Remember that we factored out an x earlier, so the entire thing is x(x+4)(x-6)
2007-01-20 13:29:16
·
answer #2
·
answered by dennismeng90 6
·
1⤊
1⤋
I assume you have to factor, correct? x^3 - 2x^2 - 24x
First: find the least common factor which is "x"
x(x^2 - 2x - 24)
Sec: factor the expression in parenthesis > multiply the 1st & 3rd coefficient to get "- 24". Find two numbers that give you
"-24" when multiplied and the 2nd/middle coefficient (-2) when added/subtracted. The numbers are: "-6 and 4"
*Rewrite the expression with the new middle coefficients...
(x^2 - 6x + 4x - 24)
Third: when you have 4 terms - group "like" terms...
(x^2 - 6x) + (4x - 24)
x(x - 6) + 4(x - 6)
(x - 6)(x+4)
*Also, please remember to combine the x-variable that was factored earlier.
x(x - 6)(x + 4)
P.S. You don't find the values for the x-variables because the original expression is not set to equal zero.
2007-01-20 13:58:12
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
x^3 - 2x^2 - 24x = x(x^2 - 2x - 24) = x(x - 6)(x + 4)
2007-01-20 13:45:03
·
answer #4
·
answered by Sherman81 6
·
1⤊
0⤋
x³-2x²-24x =
x(x² - 2x - 24) = 0
delta = (-2)² - 4.1.-24
delta = 4 + 96
delta = 100
x = (2 +/- sqrt 100) : 2
x' = (2 + 10) : 2 = 6
x" = (2 - 10) : 2 = -4
Solution: {x elements of R | x' = 6, x" = -4 and x"' = 0}
><
2007-01-20 14:05:27
·
answer #5
·
answered by aeiou 7
·
0⤊
1⤋
x^3 - 2x^2 - 24x
= x(x - 6)(x + 4)
2007-01-20 13:35:20
·
answer #6
·
answered by wind_liao 2
·
1⤊
0⤋
f(x) = x(x^2 - 2x - 24) = x(x + 4)(x - 6) roots - 4, 0, 6
2016-05-24 02:43:07
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
Factor out an x:
x(x^2-2x-24)
x(x+4)(x-6)
Set it to zero:
x(x+4)(x-6)=0
x=0
x+4=0
x-6=0
x=0,-4, and 6
2007-01-20 13:52:05
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋
x=-4
x=6
x=0
2007-01-20 13:14:52
·
answer #9
·
answered by sandeepownzzz 1
·
1⤊
1⤋
x = 12 i think, (you factor it out two times)
2007-01-20 13:16:03
·
answer #10
·
answered by Anonymous
·
0⤊
2⤋